Tracing Patterns of Intra-Speaker Variation in Early English Correspondence: A Change from Above in the Paston Letters - Hernández-Campoy, Juan M.; Conde-Silvestre, J. Camilo; García-Vidal, Tamara (Studia Anglica Posnaniensia, 2019)
The aim of this paper is to explore the impact of social and context factors on the diffusion of a linguistic change from above, namely the deployment of the spelling innovation in fifteenth-century English, and especially in some letters from the well-known Paston collection of correspondence. We particularly focus on the socio-stylistic route of this change from above, observing the sociolinguistic behaviour of some letter writers (members of the Paston family) in connection with the social-professional status of their recipients, the interpersonal relationship with them, as well as the contexts and styles of the letters. In this way, different dimensions of this change from above in progress in fifteenth-century English can be reconstructed.